2011
DOI: 10.3141/2205-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effects of Recycled Concrete Aggregate on Volumetrics of Hot-Mix Asphalt

Abstract: Each year around 200 million tons of demolition wastes are produced from aging U.S. infrastructures. Of that amount, 100 million tons are portland cement concrete debris. Disposal of these wastes in landfills has been a traditional solution, but environmental regulations, costs, and a lack of landfill areas have hindered safe disposal. These problems have led to a search for alternate ways of reusing demolition wastes by recycling. Recycling the concrete waste not only reduces the waste disposal problem but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 3 publications
0
23
0
4
Order By: Relevance
“…As far as the ecological and financial implications are concerned, CAM can be further improved when produced with 100% recycled materials from Construction and Demolition Waste Aggregates (CDWA 4 ). Research on HMA with recycled aggregates from waste materials has experienced extensive and growing success recently (Bhusal et al, 2011;Chen et al, 2011;Liu et al, 2012;Mills-Beale and You, 2010;Modarres et al, 2015;Paranavithana and Mohajerani, 2006;Pérez et al, 2010;Pérez et al, 2012;Wong et al, 2007), thus reinforcing this new approach within pavement engineering. To a lesser extent, and although more research in this regard is necessary, different studies on CAM with recycled aggregates can also be found at present (Gómez-Meijide and Pérez, 2014b;Gómez-Meijide et al, 2015;Modarres and Ayar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As far as the ecological and financial implications are concerned, CAM can be further improved when produced with 100% recycled materials from Construction and Demolition Waste Aggregates (CDWA 4 ). Research on HMA with recycled aggregates from waste materials has experienced extensive and growing success recently (Bhusal et al, 2011;Chen et al, 2011;Liu et al, 2012;Mills-Beale and You, 2010;Modarres et al, 2015;Paranavithana and Mohajerani, 2006;Pérez et al, 2010;Pérez et al, 2012;Wong et al, 2007), thus reinforcing this new approach within pavement engineering. To a lesser extent, and although more research in this regard is necessary, different studies on CAM with recycled aggregates can also be found at present (Gómez-Meijide and Pérez, 2014b;Gómez-Meijide et al, 2015;Modarres and Ayar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies agree that it is possible to use RCA to manufacture HMA. However, HMA made with RCA displays increased optimum bitumen content than mixtures made with only with natural aggregates [7,[9][10][11][12][13][14][15]. The high porosity of the attached mortar [7,15] appears as mainly responsible for this increased bitumen consumption.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the asphalt content of the mixture is optimised [10]. The optimal asphalt content is contingent upon RCA particle size [11], as smaller particles have a larger surface area-to-volume ratio [12].…”
Section: Introductionmentioning
confidence: 99%